Aerodynamic drag reduction in winter sports: The quest for "free speed." - Brownlie, L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The Winter Olympics are a highly competitive sporting environment where subtle improvements in performance can impact the finishing order in many events. Aerodynamic drag is known to be a significant resistive force to human movement in high-speed sports, such as alpine skiing, speed skating and bobsleigh. Aerodynamic drag also represents an important determinant of performance in sports such as ice hockey, snowboard cross and cross-country skiing. From 2000 to 2018, a series of wind tunnel-based research projects were conducted to provide aerodynamically optimized apparel, equipment and wind tunnel simulation training to elite Canadian and American winter sports athletes involved in bobsleigh, skeleton, luge, ice hockey, speed skating, cross-country, alpine and para-alpine skiing, biathlon, ski-cross and snowboard cross. This article reviews the role of aerodynamic drag in winter sports, considers fundamental principles of air flow around bluff bodies and methods of drag reduction in ice and snow sports, while providing experimental results from an extensive database of wind tunnel investigations. Deficits in the literature suggest productive areas for future research to improve athletic performance in these sports.